1981
DOI: 10.1159/000198590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Lithogenic Diet on Cell Proliferation in the Murine Gallbladder Epithelium

Abstract: A cholesterol-cholic acid lithogenic diet was administered to mice for periods from 2 days to 12 weeks. Intraperitoneal injections of tritiated thymidine and autoradiographs were used for the estimation of the proliferative parameters in the gallbladder epithelium. The total DNA content of the gallbladder was determined. Significantly higher labeling (p < 0.01) and mitotic (p < 0.01) indices were observed from the 2nd day and the total DNA content of the gallbladder was increased (p < 0.01) from the 2nd week o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It was proposed but not proved that increased bile secretion was involved but this dilatation remains unexplained. Also in the latter study there was no correlation between the degree of distension of the gallbladder and the proliferative parameters (Putz and Willems, 1981a).…”
Section: Influence Of Chemical Factorsmentioning
confidence: 59%
“…It was proposed but not proved that increased bile secretion was involved but this dilatation remains unexplained. Also in the latter study there was no correlation between the degree of distension of the gallbladder and the proliferative parameters (Putz and Willems, 1981a).…”
Section: Influence Of Chemical Factorsmentioning
confidence: 59%
“…Moreover, the enhancement of mucus secretion and an increase in mitosis before the formation of any precipitate have been described (Freston et al, 1969;Lee and Scott, 1982;Lee et al, 1981b;Pemsingh et al, 1987b;Putz and Willems, 1981;Scott, 1976). By using 3 H-glucosamine, Malet et al (1989) demonstrated that, in animals fed with a cholesterol-rich diet, mucin production increases twofold and sevenfold after 1 and 3 weeks, respectively.…”
Section: Role Of Gallbladder Mucus Secretion In Gallstone Formationmentioning
confidence: 87%
“…DNA synthesis and mitotic growth were further shown to be stimulated in vivo in the epithelial cells of murine gallbladder mucosa during feeding of a cholester ol-cholic acid lithogenic diet [119] and after chronic administration of cholecystokinin-octapeptide (CCK) or caerulein, a CCK analogue [120]. Chronic administra tion of 1.0% lithocholic acid in a low-protein diet to rats produced an intrahepatic biliary hyperplasia and peri cholangitis in vivo [121], but lithocholic acid was found to be toxic to primary cultures of normal rat intrahepatic bile ducts when added at concentrations above 0.5 mM and without effect below these concentrations [99].…”
Section: Growth Properties Of Biliary Epithelial Cells and Oval Cellsmentioning
confidence: 98%